Practice as research in the arts: Principles, protocols, pedagogies, resistances - Nelson, Robin (Hampshire Palgrave Macmillan, 2013)
This book takes a fresh 'how to' approach to Practice as Research. At the 'performance turn' it argues that old prejudices should be abandoned and that a PaR methodology and its modes of 'doing-knowing' should be fully accepted in the academy. It refines Robin Nelson's earlier models for PaR but sustains the dynamic and dialogic interplay between different modes of knowledge-production in a multi-mode research inquiry. It advances strategies for articulating and evidencing the research inquiry and offers practical guidance to practitioner-researchers on how to conduct a PaR inquiry. With reference to examples drawn from a decade of supervisory, examining and audit experience, Nelson addresses - and offers answers to - the many questions students, professional practitioner-researchers, regulators and examiners have posed in this domain. To broaden the perspective and take account of differing levels of acceptance and development of programmes in PaR around the word, in Part II of the book six international contributors respond to Part I and afford cross-sights from the standpoint of their territory (covering the US, Europe, South Africa and New Zealand).